Fixed Point Theorems for Multivalued Mappings Involving α-Function - Muhammad Usman Ali; Quanita Kiran; Naseer Shahzad (Abstract and Applied Analysis)
We obtain some fixed point theorems with error estimates for multivalued mappings satisfying a new α-ψ-contractive type condition. Our theorems generalize many existing fixed point theorems, including some fixed point theorems proved for α-ψ-contractive type conditions.